Changes in severity of clinical pattern of dengue infection and its management: a cross-sectional study in a tertiary care hospital - Hossain, M. D.; Chowdhury, M. D. Shafiqul Alam; Hossen, Kamal; Chowdhury, Pujanjali (International Journal of Contemporary Pediatrics, 2022)
Background: Dengue fever is a debilitating viral disease, transmitted by mosquitoes, and causes sudden fever, and acute pain in the joints. Aedes Aegyptus mosquitos are responsible for dengue fever. More than 500,000 people are affected by dengue fever each year. In Bangladesh, over 15,000 cases of dengue are reported each year. It is high time to take some measures to control this viral disease. The aim of the study was to investigate the clinical manifestation of dengue fever in tertiary care hospitals. Methods: It is a prospective cross-sectional study that was carried out in the pediatric department of Dhaka medical college hospital (DMCH) over one year and was conducted with 106 patients. Results: The finding had females dominant over males. Minimum and maximum ages were 1 and 14 respectively. All patients (106, 100%) had fever. Around one-third of the patients (34,32%) had headaches. Patients had experienced rash and vomiting. The Tourniquet test came out positive for about one-fifth of the patients (21, 19.8%). About half of the study population (50, 47.2%) had dengue fever, around two-fifth of the patients (44, 41.5%) experienced dengue hemorrhagic fever (DHF) and only 12 patients (12, 11.3%) were diagnosed with dengue shock syndrome (DSS). The majority of the patients (102, 96.22%) were given isotonic fluid. Ns1 antigen for dengue 65 cases and IgM & IgG for dengue 32 cases were positive. Conclusions: Dengue is a rapidly emerging pandemic disease in many parts of the world, especially in Bangladesh. There is no accurate treatment to treat dengue patients. However, more illness and death could be prevented if countries regularly monitor the circulation of viruses in the mosquitos and take control measures before there are consequential outbreaks.